2020
DOI: 10.1002/nbm.4266
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy in skeletal muscle: Experts' consensus recommendations

Abstract: H-MR spectroscopy of skeletal muscle provides insight into metabolism that is not available noninvasively by other methods. The recommendations given in this article are intended to guide those who have basic experience in general MRS to the special application of 1 H-MRS in skeletal muscle. The highly organized structure of skeletal muscle leads to effects that change spectral features far beyond simple peak heights, depending on the type and orientation of the muscle. Specific recommendations are given for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 115 publications
0
37
0
Order By: Relevance
“…Residual dipolar coupling: Partially detectable dipolar coupling in partially oriented molecules, where the physics is identical to dipolar coupling, but the size of the coupling is reduced by partial averaging reflecting the degree of orientation (eg, in liquid crystals or in vivo in 1 H MRS of skeletal muscle) 141,142 …”
Section: Further General Terminologymentioning
confidence: 99%
See 2 more Smart Citations
“…Residual dipolar coupling: Partially detectable dipolar coupling in partially oriented molecules, where the physics is identical to dipolar coupling, but the size of the coupling is reduced by partial averaging reflecting the degree of orientation (eg, in liquid crystals or in vivo in 1 H MRS of skeletal muscle) 141,142 …”
Section: Further General Terminologymentioning
confidence: 99%
“…Orientation dependence: Dependence of a parameter or spectrum on the orientation of the investigated object (eg, muscle fiber or microscopic non‐spherical object) with respect to B 0 141,142 …”
Section: Further General Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…Results from our previous studies, as well as from other studies, are reported in mmol/kg ww units. However, as was suggested in a recent consensus paper by Krššák et al (19), results of acetylcarnitine concentrations are given in mmol/L tissue volume units.…”
Section: Discussionmentioning
confidence: 99%
“…The Magnetic Resonance Spectroscopy Consensus Group recommended the use of sLASER at high fields (≥ 3 T) for brain [ 14 ] and musculoskeletal [ 15 ] applications to improve reproducibility of data acquisition and metabolite quantification. sLASER has the advantages to provide a considerably lower CSDE with a sharper voxel localization compared to PRESS [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%